ChemInform Abstract: Metal‐Free Synthesis of Sulfonylated Amides Through Radical Aryl Migration—Desulfonylation. Issue 38 (September 2016) - Qiu, Jiang‐Kai; Hao, Wen‐Juan; Kong, Li‐Fang; Ping, Wei; Tu, Shu‐Jiang; Jiang, Bo
Abstract: The addition of sulfonyl radicals to the double bond of acrylamides triggers a domino 5‐exo‐trig cyclization, desulfonylation, and aryl migration sequence, affording a series of sulfonylated amides.